LITERATURE REVIEW: COMPREHENSIVE UNDERSTANDING OF DYNAMICS AND CHALLENGES IN ENTREPRENEURSHIP DEVELOPMENT IN INDONESIA - Eliagus Telaumbanua; Silvia Ekasari; Henny Noviany; Dakwan Soaloon Harahap; Iwan Kusnadi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Entrepreneurship development in Indonesia is a multifaceted phenomenon influenced by various factors and characterized by opportunities and challenges. This literature review provides a comprehensive understanding of the dynamics and challenges shaping entrepreneurship in Indonesia. It explores the role of government policies, education and training programs, access to finance, supportive infrastructure, and international collaboration in fostering entrepreneurship. Additionally, the review delves into the driving factors of entrepreneurship, including cultural, economic, educational, technological, social, and regulatory dimensions. Furthermore, it examines the challenges hindering entrepreneurship development, such as access to finance, skills and talent shortages, regulatory burdens, market competition, infrastructure deficiencies, and socio-cultural constraints. By synthesizing existing literature, this review aims to provide insights into the intricacies of entrepreneurship development in Indonesia and offer recommendations for policymakers, stakeholders, and researchers to address critical challenges and unlock the full potential of the entrepreneurial ecosystem.